Peer-led education or booklet for knowledge transfer about disease: A randomized-controlled trial with ankylosing spondylitis patients - Taciser Kaya; Pınar Atıcı; Altınay Göksel Karatepe; Rezzan Günaydın (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate whether peer-led group education + booklet is superior to booklet only to increase ankylosing spondylitis (AS) patients’ knowledge about their disease. Patients and methods: A total of 56 patients (46 males, 10 females; mean age 41.9±9.2 years; range, 22 to 58 years) with a definite diagnosis of AS who were under follow-up in our outpatient clinic between August 2010 and January 2012 were included in this study. The patients were randomly allocated to the peer-led education + booklet (education group, n=27) and booklet only (control group, n=29). To assess the level of patients’ knowledge, a patient knowledge questionnaire containing four domains was used. Evaluations were made at baseline, four weeks, and six months. The variables were “number of correct choices” (NoCC), “number of correct items” (NoCI) and percent of correct choices for each domain; the later one was resembled by the name of that domain (area A, area B, etc.). Results: The variables that improved in both groups were NoCC, NoCI, and “pharmacotherapy and physical therapy area” (area C). These improvements were similar between the groups (respectively, p=0.915, p=0.830, p=0.791). Conclusion: Reading a booklet alone is as successful as peer-led education + booklet for knowledge transfer about their disease in patients with AS. In this study, the most knowledge gain was achieved in “drug treatment and physical therapy” area.